2004
DOI: 10.1107/s0907444904022292
|View full text |Cite
|
Sign up to set email alerts
|

Solution and structure of an alternatingD,L-peptide

Abstract: The crystal structure of H-(L-Tyr-D-Tyr)(4)-L-Lys-OH has been determined to 1.3 A resolution. The D,L-alternating peptide crystallizes in the tetragonal system, space group P4(3)2(1)2, with unit-cell parameters a = b = 27.99 (3), c = 78.93 (8) A. The crystals contain two molecules in the asymmetric unit that form a double-stranded right-handed antiparallel beta-helix. The structure has been solved by SIRAS using a crystal soaked in an iodide-containing solution for 1 min. The programs SHELXD and SHELXE were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The homodimeric representative of the applied peptide motif H-(Tyr- Tyr ) 4 -Lys-OH has already been shown to enable intermolecular interaction via its phenolic side-chain pattern within the aqueous phase (Alexopoulos et al 2004). The homodimer species 2 adopts a membrane spanning orientation in DLPC bilayers (Küsel et al 2007) and likewise tends to aggregation (Schneggenburger et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homodimeric representative of the applied peptide motif H-(Tyr- Tyr ) 4 -Lys-OH has already been shown to enable intermolecular interaction via its phenolic side-chain pattern within the aqueous phase (Alexopoulos et al 2004). The homodimer species 2 adopts a membrane spanning orientation in DLPC bilayers (Küsel et al 2007) and likewise tends to aggregation (Schneggenburger et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The d , l alternation of the peptide backbone concordant with a double-helical β -type shape is related to natural peptide antibiotics such as gramicidin A (Kelkar and Chattopadhyay 2007) or feglymycin (Bunkóczi et al 2005). In addition, the studied sequences are unique on their own due to their almost purely aromatic side-chain composition (Alexopoulos et al 2004; Küsel et al 2007). On the basis of the crystallographically elucidated water-soluble nonameric sequence H-(Tyr- Tyr ) 4 -Lys-OH (note: underlined amino acids indicate the d -conformer), the homodimeric dodecamer H-( Phe -Tyr) 5 - Trp -Trp-OH ( 1 ) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This observation might reflect an aggregating effect of the peptide motif that was also observed during reverse-phase chromatographic purification and has been elucidated by X-ray structural analysis of the related water-soluble peptide H-(YY) 4 K-OH. [26] The membrane surfaces observed by optical microscopy already indicated the need of a new electron-rich and site-specific label for X-ray reflectivity analysis of membrane-bound species because such labels allow for the application of lower P/L-ratio samples, yielding enhanced quality of the sample itself and of the deduced analytical data.…”
Section: Membrane Incorporation Of B 56 -Helices and X-ray Reflectivitymentioning
confidence: 99%
“…The X-ray reflectivity data resulting in case of the membrane/peptide complex of peptide 8 show two outliers with the samples P/L = 1/100 and 1/10, but an increase in membrane thickness can clearly be observed and might result from hydrophobic mismatching. [26][27][28][29][30][31][32] Considering that the membrane thickness is a function of distance between the anchoring peptide elements at the membrane polar/unpolar interface, a slight increase in membrane thickness is in line with a peptide b-helical structure that fits the carbonyl-glycerol distance of a DLPC bilayer. [24,[33][34][35][36][37][38] For the samples with incorporated peptides, a decrease in the electron-density contrast of the side to the main minima (shape parameter E) is observed as in most peptide/ lipid systems.…”
Section: Membrane Incorporation Of B 56 -Helices and X-ray Reflectivitymentioning
confidence: 99%
“…They were integrated with D*TREK (18) and scaled with SCALA (19). Although data completeness is significantly lower for the outer resolution shell than the overall completeness (Table 1), it is not uncommon to use diffraction data with completeness of 75% or less for the entire dataset (20)(21)(22)(23)(24) and of 20-45% for the highest-resolution shell (22)(23)(24)(25), especially when experimental data or a higher-resolution structure is available for phasing. It has been shown that inclusion of weaker high-resolution reflections improves maximum-likelihood-based refinements (26) because it significantly increases the amount of unique data against which the model is refined.…”
Section: Methodsmentioning
confidence: 99%